Pengaruh Motivasi Intrinsik, Disiplin Kerja, Fasilitas Kerja dan Kompensasi Finansial terhadap Kinerja Karyawan CV. Alrava Albasia - Nadhea Yogy Paramita (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of this research is to find out and explain whether there is an influence between the variables of intrinsic motivation, work discipline, work facilities, and financial compensation on the performance of employees of CV. Alrava Albasia. The population used in this research is all employees of CV. Alrava Albasia, numbering 80 people. A sample of 80 people and using saturated sampling technique. The analysis technique used is validity test, reliability test, normality test, multicollinearity test, hetoroscedasticity test, autocorrelation test, multiple linear regression analysis, t test (partial), F test (simultaneous). From the results of the study it was obtained that partially there is a significant influence between intrinsic motivation on employee performance, this can be seen from the significant value t of 0.012 <0.05 work discipline has a significant influence on employee performance with a significant value of 0.005 <0.05 work facilities has a significant influence on employee performance with a significant value of 0.010 <0.05 financial compensation has a significant influence on employee performance with a significant value of 0.000 <0.05. Intrinsic motivation, work discipline, work facilities and financial compensation simultaneously affect the performance of CV employees. Alrava Albasia with a significant F value of 0.000<0.05.